The anthropometric status and dietary intake of adults engaging in bodybuilding programme around Polowane Municipality in Limpopo Province - Masoga, Sylven (My University, 2017)
Introduction: Bodybuilders around Polokwane municipality are adhering to different dietary practices some of which are not evidence based. These practices may predispose these athletes to negative health outcomes sooner or later in life. The aim of this study was to investigate the anthropometric status and dietary intake of bodybuilders around Polokwane Municipality. Methodology: This was a descriptive analytical study where purposive sampling method was used to obtain 51 out of 65 registered bodybuilders within the training gyms around Polokwane. Weight and Height were measured to determine BMI. Four skinfold sites (triceps, biceps, subscapular and suprailliac) were measured using caliper and non-stretchable tape to estimate total body fat percentage. Dietary information was collected using the 24 hour-recall collected for three different days which was validated by the Food Frequency Questionnaire. Results: of the 51 body builders, 94.1% were men and 5.8% women. Few athletes (15.7%) were using ergogenic agents such as powders (13.7%) and tablets (2%). Also, 64.7% of the athletes had normal body weight while 33.3% and 2.0% were overweight and obese respectively. Majority of the athletes (78.4%) had an acceptable body fat percentage. Dietary results showed that majority of the athletes consumed energy (98%) and carbohydrates (100%) below the ISSN bodybuilding recommendations. Conclusion: The dietary intake of the bodybuilding athletes around Polokwane municipality is below the ISSN (2010) bodybuilding recommendations; however, their anthropometric status and body composition is normal.
Thesis (M. Sc. (Dietectics)) -- University of Limpopo, 2017
Keywords: Bodybuilders; Anthropometry; Body fat; Energy; Carbohydrates; Protein; Micronutrients; Supplements; Reducing diets; Body mass index; Aboriginal Australians -- Anthropometry; Nutrition